A rare case of Kimura lymphadenpathy in elderly female - Ganesan, Vinayagam; Periyasamy, Venkatesh Sadayan; Kannaian, Muralidharan (International Surgery Journal, 2020)
Kimura’s disease (KD) is a chronic inflammatory disease, a rare variety. It usually presents as non-tender subcutaneous swelling in head and neck region, predominantly in preauricular and submandibular area and is often associated with cervical lymphadenopathy, marked peripheral eosinophilia and an elevated immunoglobulin E (IgE) level. Renal involvement is the only systemic manifestation.4 Nephrotic syndrome is the most common manifestation of renal disease in KD. Diagnosis through Fine needle aspiration cytology (FNAC) is misleading and can easily be mistaken as a malignant disease. So, diagnosis is therefore only established by histopathological examination. The treatment of KD involves one of three major approaches are surgical excision, irradiation, or steroid therapy. Surgical excision is recommended as the treatment of choice but carries recurrence rates of 33-50%. In our study, we are reporting a case of elderly female who presented with left sided cervical lymphadenopathy for which excision biopsy was done and the histopathology examination shown as kimura lymphadenopathy, a rare case.